Pengaruh Jumlah Kunjungan Wisatawan dan Objek Wisata Terhadap Pendapatan Asli Daerah Daerah Istimewa Yogyakarta - Wahyuni, Sri; Lestari, Heni Dwi; Susilo, Susilo (Pringgitan, 2023)
This study aims to measure the impact of the number of tourist visits and tourist attractions on increasing the local revenue of the Special Region of Yogyakarta Province for the period 2019-2023. This research uses secondary data obtained from an tourism office in the Special Region of Yogyakarta. Sampling in this study was conducted in all districts in the Special Region of Yogyakarta. This research technique uses linear regression analysis. The research found that the variable number of visits has a positive effect on the original income and tourism has a negative effect on the original income. Meanwhile, tourist attractions have no effect on indigenous income. New research was conducted in Yogyakarta Special Region Province, which has been conducted to find out how effective financial governance is in the development and development of the tourism sector.Keywords: Tourist Visit; Tourist Attraction; Local Revenue